Effectiveness of Autologous Platelet-Rich Plasma for the Healing of Ulcers after Endoscopic Submucosal Dissection - Eunju Jeong; In kyung Yoo; Ozlem Ozer Cakir; Hee Kyung Kim; Won Hee Kim; Sung Pyo Hong; Joo Young Cho (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims Platelet-rich plasma (PRP) has been used for wound healing in various medical fields. The aim of this study was to evaluate the clinical efficacy and safety of local PRP injections after endoscopic submucosal dissection (ESD). Methods Patients were non-randomly divided into the following two groups: (1) control group in which patients were administered only an intravenous proton pump inhibitor (PPI), and (2) a study group in which patients were administered an intravenous PPI and a topical PRP injection. We assessed the reduction in the ulcer area and stage of the ulcer after the procedure (24 hours, 48 hours, and 28 days after endoscopic surgery). Results We enrolled 7 study and 7 control patients. In the study group, the rate of ulcer reduction was 59% compared to 52% in the control group (p=0.372), 28 days after ESD. There were 5 patients in the S stage and 2 patients in the H stage in the study group compared to no patient in the S stage and 7 patients in the H stage in the control group (p=0.05), 28 days after ESD. There were no serious complications in either group. Conclusions The local injection of PRP is a safe and effective procedure for ulcer healing after ESD.